E-Modul Based Flipped Classroom Learning Models in Vocational Education - ., Ambiyar; ., Waskito; Rojiyyah, Iffah; Efendi, Raimon; Wulandari, Ratih Agustin (KnE Social Sciences, 2023)
This research is motivated by the lack of innovative learning media used in that it is still less innovative, only using media available in the environment and not utilizing technology. The aim of this research is to produce an E-Module oriented to the flipped classroom model that can improve students’ achievement of 21st century competencies. This study used a development research design with the ASSURE development model. The results showed that the E-Module oriented to the flipped classroom model using the Kvisoft Flipbook Maker application in learning computer network security developed met valid criteria with the characteristics of the media content in accordance with the curriculum, clear design and layout, ease of media operation, clear language. , simple, concise, easy to understand, and the presentation is clearly adapted to the characteristics of students. The results of observations and questionnaires show that the learning media is practical with characteristics that have clear content and objectives, are easy to read, have an attractive appearance and can increase student attractiveness and interest in learning computer network security. In addition, the media developed has also been effective in increasing student activity and learning outcomes and the 21st century students’ learning competencies have also increased. Keywords: Flipped; Classroom learning; learning competencies